Jupiter's legacy. Volume 1 - Millar, Mark (Image Comics, Inc., 2020)
"In mid-century America, the world's greatest superheroes face epic threats in public while battling private scandals behind closed doors. Now adapted into a big-budget Netflix Original series, get in on the ground floor with one of the most critically acclaimed superhero series of the past 10 years"--Publisher's website.